Toward the innovative firm-challenge for R&D management - Kumpe, Ted
Ted Kumpe and Piet T. Bolwijn foresee an increasingly pivotal role for R&D as large industrial firms come to compete on the basis of their innovative ability.
An analysis of the changing character of international competition shows how and why success is increasingly dependent upon the R&D function.
Industrial strategies for multinationals have undergone profound changes. Underlying causes are to be found in new market factors, technological developments and intensified competition. More and more, it is recognized that companies that companies are confronted with increasing demands for efficiency, quality and flexibility. Product prices are under continuous pressure, ever-higher quality standards are simply a must, and the rate of product renewal has increased considerably. Under these conditions, it is increasingly difficult for companies to distinguish themselves from competitors. Innovation proves to be the magic word. This places R&D in the midst of the competitive battle, dramatically changing the role of the R&D function.
Keywords: R&D management